Recognizing benign and malignant skin lesions: Effect of a dermoscopy training course for general practitioners - Marjolein S. Bruijn; Els Visser; Wouter K. van der Heide (Wiley, 2024)
Abstract Background The incidence of skin cancer is rapidly increasing, leading to a growing amount of general practitioner (GP) consultations of patients with suspected skin lesions. It is essential that GPs have good training skills to differentiate between benign and malignant skin lesions. Dermoscopy in addition to clinical examination can help them to develop these skills. Objectives In this article, we examine the effect of a 2‐day training course in dermoscopy among Dutch GPs. Methods The educational intervention was designed as blended learning and consisted of a 2‐day training course on dermoscopy, clinical features, and management of patients with suspected skin lesions in primary care. Before the training course, all participants were required to take a test (T0). This test was repeatedly administered at the end of the second course day (T1) and within 6 months after completion of the course (T2). Outcomes were the specificity and sensitivity of recognizing skin lesions and the changes between the test moments. Results In total, 400 GPs participated in the training course. At T1, the specificity for detecting benign lesions was higher than at T0 (0.91 vs. 0.75). This specificity remains at the same level at T2, 6 months after the course (0.91 p < 0.001). The sensitivity for detecting malignant lesions stayed about the same level: 0.80 at T0 and 0.84 at T2 (p < 0.001). Conclusions The results of our study show a sustaining positive effect of a 2‐day training course on detecting benign skin lesions by GPs.